Hydrophobic tear-resistant biodegradable copolyester material and preparation method thereof
By introducing castor oil into the fat-aromatic copolyester molecular structure and using isocyanate to form a branched structure, the problem of degradation of mechanical properties of fat-aromatic copolyester materials after hydrolysis is solved, and the material's resistance to hydrolysis and tear resistance is improved.
Patent Information
- Application Number
- CN202411649653.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-19
- Publication Date
- 2025-03-11
AI Technical Summary
The existing fat-aromatic copolyester materials have decreased mechanical properties after hydrolysis, insufficient tear resistance, and are easy to absorb moisture in the air, shortening their service life.
Castor oil is introduced into the fat-aromatic copolyester molecular structure through isocyanate to form hydrophobic, tear-resistant biodegradable copolyester materials, improving its anti-hydrolysis and tear resistance.
It significantly improves the hydrolysis and tear resistance of the material, extends the shelf life and service life of the product, and avoids the decline in mechanical properties.
Smart Images

Figure BDA0005140567250000031 
Figure BDA0005140567250000071 
Figure BDA0005140567250000081
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of biodegradable materials, and in particular relates to a hydrophobic and tear-resistant biodegradable copolyester material and a preparation method thereof. Background Art
[0002] The accelerated pace of life has led to a sharp increase in the consumption of disposable plastic products. These plastic products cannot be decomposed in nature after being discarded, resulting in an increase in plastic waste year by year and worsening environmental pollution. With the increase in environmental awareness, how to solve and suppress the emergence of plastic waste has become one of the most important issues of concern to people, and biodegradable materials have emerged. Biodegradable materials can be decomposed into water and carbon dioxide by microorganisms in the natural environment, which is of great significance to reducing plastic pollution. Plastic films, plastic bags and other products are commonly used disposable plastic products in life, and are also important application areas for biodegradable materials.
[0003] Degradable polymer materials include aliphatic polyesters, polyester ethers, polyphosphazenes, polylactic acid, polycarbonates, polyanhydrides, polyamino acids, etc. Among them, aliphatic-aromatic copolyesters, such as polybutylene terephthalate adipate (PBAT), polybutylene terephthalate succinate (PBST), and polybutylene terephthalate sebacate (PBSET), have become the basic resins for manufacturing biodegradable film bag products due to their unique toughness, tensile strength and elongation, flexural strength, film tearing properties and relatively cheap prices.
[0004] However, there are a large number of ester bonds on the molecular main chain of fat-aromatic copolyesters. The unprotected ester bonds are very easy to hydrolyze, which can easily lead to the breakage of the main chain of the polymer molecular chain and the decline of mechanical properties. At the same time, fat-aromatic copolyesters are mostly linear molecules, and the tear resistance of the prepared film bag products is still somewhat lower than that of the film bags prepared by traditional polyethylene. In addition, when fat-aromatic copolyester products are exposed to air, they will slowly absorb moisture in the air, causing the moisture content to gradually increase to several thousand ppm, promoting the occurrence of hydrolysis reactions, and inevitably shortening the shelf life and service life of the products. Therefore, how to control the hydrolysis aging rate of fat-aromatic copolyesters, improve their tear resistance, and avoid the decline of mechanical properties or even unusability during normal storage and use is of practical significance. Summary of the invention
[0005] The purpose of the present invention is to provide a hydrophobic, tear-resistant biodegradable copolyester material in view of the above technical problems. Castor oil is introduced into the molecular structure of the fat-aromatic copolyester through isocyanate, thereby improving the hydrolysis resistance and tear resistance of the fat-aromatic copolyester material.
[0006] The hydrophobic and tear-resistant biodegradable copolyester material in the technical solution of the present invention comprises the following raw materials in parts by weight: 90 to 99 parts of aliphatic-aromatic copolyester, 0.5 to 5.0 parts of castor oil, and 0.5 to 5.0 parts of isocyanate.
[0007] Furthermore, the aliphatic-aromatic copolyester is obtained by esterification and polycondensation of aromatic acid, fatty acid and alcohol compound.
[0008] Furthermore, the molar ratio of aromatic acid to fatty acid in the aliphatic-aromatic copolyester is 1-50:50-99.
[0009] Furthermore, the molar amount of the alcohol compound is 1.0 to 5.0 times, preferably 1.5 to 2.0 times, the sum of the molar amounts of the aromatic acid and the fatty acid.
[0010] Preferably, the aromatic acid is an aromatic dibasic acid, including but not limited to one or more of terephthalic acid, phthalic acid, and isophthalic acid.
[0011] Preferably, the fatty acid is an aliphatic dibasic acid, including but not limited to one or more of succinic acid, adipic acid, sebacic acid, and azelaic acid.
[0012] Preferably, the alcohol compound is an aliphatic diol, including but not limited to one or more of 1,4-butanediol, 1,4-pentanediol, propylene glycol, and hexanediol.
[0013] Furthermore, the temperature of the esterification reaction is 200-300° C., preferably 230-250° C., and the reaction is carried out until no esterification water is generated and the materials in the reactor are completely clarified.
[0014] Furthermore, the temperature of the polycondensation reaction is 200 to 300° C., preferably 240 to 260° C., the absolute pressure is 80 to 120 Pa, and the reaction time is 1 to 10 h.
[0015] Preferably, the preparation method of aliphatic-aromatic copolyester comprises the following steps: adding an alcohol compound to an esterification reactor, adding aromatic acid, fatty acid and catalyst in sequence under stirring, heating to carry out esterification reaction, transferring the obtained esterified product to a polycondensation reactor, stirring, heating and slowly reducing pressure to carry out polycondensation reaction; the catalyst includes but is not limited to one or more of tetrabutyl titanate, tetraisopropyl titanate, complex titanium and Ti / Si composite; the mass of the catalyst is 0.01-0.03% of the sum of the mass of aromatic acid, fatty acid and alcohol compound; the stirring speed is 50-100 rpm.
[0016] Furthermore, the melt flow rate (MFR) of the aliphatic-aromatic copolyester at 190° C. and a load of 2.16 kg is 20 to 100 g / 10 min.
[0017] Furthermore, the carboxyl content in the aliphatic-aromatic copolyester is ≤30 mol / t; preferably, the carboxyl content in the aliphatic-aromatic copolyester is 5 to 30 mol / t.
[0018] The main component of the castor oil is ricinoleic acid triglyceride, as shown in formula (1):
[0019]
[0020] The long carbon chain hydrophobic groups in castor oil triglyceride can protect the main chain of the fat-aromatic copolyester, reduce its moisture absorption capacity, and improve its resistance to hydrolysis, which is beneficial to extend the shelf area and service life of the product; at the same time, the trihydroxy structure in ricinoleic acid triglyceride can be connected with the fat-aromatic copolyester through isocyanate to form a branched structure or a micro-cross-linked structure, thereby improving the strength and tear resistance of the fat-aromatic copolyester products.
[0021] Furthermore, the isocyanate is one or more of diphenylmethane diisocyanate (MDI), toluene diisocyanate (TDI), hexamethylene diisocyanate (HDI), isophorone diisocyanate (IPDI), and dicyclohexylmethane diisocyanate (HMDI).
[0022] Furthermore, the hydrophobic and tear-resistant biodegradable copolyester material further comprises 0.0 to 0.5 parts of an initiator.
[0023] Preferably, the amount of the initiator in the hydrophobic, tear-resistant biodegradable copolyester material is 0.1 to 1.0 parts.
[0024] A large number of carbon-carbon double bonds are retained in the aliphatic-aromatic copolyester. During the product processing, a pre-embedded initiator can be used to initiate a second grafting or cross-linking to further improve its strength and tear resistance.
[0025] Furthermore, the initiator is a peroxide initiator, including but not limited to one or more of di-(tert-butylperoxyisopropyl)benzene (BIBP), methyl ethyl ketone peroxide (MEKP), di-tert-butyl peroxide (DTBP), and diisopropylbenzene peroxide (DCP).
[0026] The present invention also provides a method for preparing the hydrophobic and tear-resistant biodegradable copolyester material, comprising the following steps: adding aliphatic-aromatic copolyester to a feeding bin of a twin-screw extruder, adding castor oil to a storage tank A connected to a melting section of the twin-screw extruder, adding isocyanate to a storage tank B connected to a plasticizing section of the twin-screw extruder, and starting the twin-screw extruder for mixing, melting, extruding, cooling, and pelletizing.
[0027] Preferably, the initiator and the aliphatic-aromatic copolyester are added together into the feed bin of the twin-screw extruder.
[0028] Furthermore, the temperature of the twin-screw extruder for mixing, melting and extruding is 120-180°C.
[0029] Furthermore, the length-to-diameter ratio L / D of the twin-screw extruder is ≥48.
[0030] Compared with the prior art, the technical solution of the present invention has the following beneficial effects:
[0031] (1) Castor oil is introduced into the molecular structure of aliphatic-aromatic copolyester by isocyanate, thereby improving the hydrolysis resistance and tear resistance of the aliphatic-aromatic copolyester material, and obtaining a hydrophobic, tear-resistant biodegradable copolyester material;
[0032] (2) The long carbon chain hydrophobic groups in castor oil triglyceride, the main component of castor oil, can protect the main chain of the fat-aromatic copolyester, reduce its moisture absorption capacity, and improve its hydrolysis resistance, which is beneficial to extend the shelf area and service life of the product;
[0033] (3) The trihydroxy structure in ricinoleic acid triglyceride, the main component of castor oil, can be connected with the fat-aromatic copolyester through isocyanate to form a branched structure or a micro-crosslinked structure, thereby improving the strength and tear resistance of the fat-aromatic copolyester products;
[0034] (4) A large number of carbon-carbon double bonds are retained in the aliphatic-aromatic copolyester. During the product processing, the initiator pre-embedded in the copolyester material preparation process can initiate a second grafting or cross-linking, further improving the strength and tear resistance of the product;
[0035] (5) The preparation method of the hydrophobic and tear-resistant biodegradable copolyester material is simple and easy to operate and suitable for industrial application. DETAILED DESCRIPTION
[0036] The technical scheme of the present invention is further described below by specific embodiments. It should be understood that the specific embodiments described herein are only used to help understand the present invention and are not intended to be used for specific limitations of the present invention. Unless otherwise specified, the raw materials used in the embodiments of the present invention are all commonly used raw materials in the art, and the methods used in the embodiments are all conventional methods in the art.
[0037] The preparation method of the fat-aromatic copolyester in the following examples comprises the following steps:
[0038] (1) 1,4-butanediol is added to an esterification reactor, and terephthalic acid, an aliphatic dibasic acid (specific terephthalic acid and aliphatic dibasic acid are as described in the embodiment) and tetrabutyl titanate are added in sequence under stirring at 80 rpm, and the temperature is raised to 240° C. for esterification reaction, and the reaction is carried out until no esterification water is generated and the material in the reactor is completely clarified to obtain an esterified product; the molar amount of 1,4-butanediol is 2.0 times the sum of the molar amounts of terephthalic acid and the aliphatic dibasic acid, and the mass of tetrabutyl titanate is 0.02% of the sum of the mass of terephthalic acid, the aliphatic dibasic acid and 1,4-butanediol;
[0039] (2) The obtained esterified product was transferred to a polycondensation reactor, heated to 250° C. with stirring at 80 rpm, and then slowly reduced to 100 Pa for polycondensation reaction for 5 hours. The carboxyl content of the obtained aliphatic-aromatic copolyester was 5 to 30 mol / t. At the same time, the MFR of the aliphatic-aromatic copolyester was adjusted to the required range in the embodiment.
[0040] Example 1
[0041] The preparation method of the hydrophobic and tear-resistant biodegradable copolyester material of the present embodiment comprises the following steps: adding 95.5 parts of poly(hexamethylene terephthalate adipate) (MFR is 30-40 g / 10 min, and the molar ratio of terephthalic acid to adipic acid is 45:55) into a feeding bin of a twin-screw extruder, adding 2.0 parts of castor oil into a storage tank A connected to the melting section of the twin-screw extruder, adding 2.5 parts of MDI into a storage tank B connected to the plasticizing section of the twin-screw extruder, setting the temperature of the twin-screw extruder to 120-150° C., and starting the twin-screw extruder for mixing, melting, extruding, cooling, and pelletizing.
[0042] Example 2
[0043] The preparation method of the hydrophobic and tear-resistant biodegradable copolyester material of the present embodiment comprises the following steps: adding 95.5 parts of poly(hexylene terephthalate adipate) (MFR is 30-40 g / 10 min, and the molar ratio of terephthalic acid to adipic acid is 45:55) and 0.2 parts of BIBP into a feeding bin of a twin-screw extruder, adding 2.5 parts of castor oil into a storage tank A connected to the melting section of the twin-screw extruder, and adding 2.0 parts of TDI into a storage tank B connected to the plasticizing section of the twin-screw extruder, setting the temperature of the twin-screw extruder to 120-150° C., and starting the twin-screw extruder for mixing, melting, extruding, cooling, and pelletizing.
[0044] Example 3
[0045] The preparation method of the hydrophobic and tear-resistant biodegradable copolyester material of the present embodiment comprises the following steps: adding 95.5 parts of polybutylene terephthalate succinate (MFR is 30-40 g / 10 min, and the molar ratio of terephthalic acid to succinic acid is 25:75) into a feeding bin of a twin-screw extruder, adding 2.5 parts of castor oil into a storage tank A connected to the melting section of the twin-screw extruder, adding 2.0 parts of MDI into a storage tank B connected to the plasticizing section of the twin-screw extruder, setting the temperature of the twin-screw extruder to 120-150° C., and starting the twin-screw extruder for mixing, melting, extruding, cooling, and pelletizing.
[0046] Example 4
[0047] The preparation method of the hydrophobic and tear-resistant biodegradable copolyester material of the present embodiment comprises the following steps: adding 95.5 parts of polybutylene terephthalate sebacate (MFR is 50-60 g / 10 min, and the molar ratio of terephthalic acid to sebacic acid is 47.5:52.5) into the feeding bin of a twin-screw extruder, adding 2.5 parts of castor oil into a storage tank A connected to the melting section of the twin-screw extruder, adding 2.0 parts of MDI into a storage tank B connected to the plasticizing section of the twin-screw extruder, setting the temperature of the twin-screw extruder to 120-150° C., and starting the twin-screw extruder for mixing, melting, extruding, cooling, and pelletizing.
[0048] Example 5
[0049] The preparation method of the hydrophobic and tear-resistant biodegradable copolyester material of the present embodiment comprises the following steps: adding 95.5 parts of poly(hexylene terephthalate adipate) (MFR is 80-100 g / 10 min, and the molar ratio of terephthalic acid to adipic acid is 45:55) into a feeding bin of a twin-screw extruder, adding 2.5 parts of castor oil into a storage tank A connected to the melting section of the twin-screw extruder, and adding 2.0 parts of HDI into a storage tank B connected to the plasticizing section of the twin-screw extruder, setting the temperature of the twin-screw extruder to 120-150° C., and starting the twin-screw extruder for mixing, melting, extruding, cooling, and pelletizing.
[0050] Example 6
[0051] The preparation method of the hydrophobic and tear-resistant biodegradable copolyester material of the present embodiment comprises the following steps: adding 94.8 parts of poly(hexylene terephthalate adipate) (MFR is 30-40 g / 10 min, and the molar ratio of terephthalic acid to adipic acid is 45:55) into a feeding bin of a twin-screw extruder, adding 3.0 parts of castor oil into a storage tank A connected to the melting section of the twin-screw extruder, adding 2.2 parts of MDI into a storage tank B connected to the plasticizing section of the twin-screw extruder, setting the temperature of the twin-screw extruder to 120-150° C., and starting the twin-screw extruder for mixing, melting, extruding, cooling, and pelletizing.
[0052] Example 7
[0053] The preparation method of the hydrophobic and tear-resistant biodegradable copolyester material of the present embodiment comprises the following steps: adding 96.8 parts of poly(hexamethylene terephthalate adipate) (MFR is 30-40 g / 10 min, and the molar ratio of terephthalic acid to adipic acid is 45:55) into a feeding bin of a twin-screw extruder, adding 2.0 parts of castor oil into a storage tank A connected to the melting section of the twin-screw extruder, adding 1.2 parts of MDI into a storage tank B connected to the plasticizing section of the twin-screw extruder, setting the temperature of the twin-screw extruder to 120-150° C., and starting the twin-screw extruder for mixing, melting, extruding, cooling, and pelletizing.
[0054] Example 8
[0055] The preparation method of the hydrophobic and tear-resistant biodegradable copolyester material of the present embodiment comprises the following steps: adding 94.0 parts of poly(hexamethylene terephthalate adipate) (MFR is 30-40 g / 10 min, and the molar ratio of terephthalic acid to adipic acid is 45:55) into a feeding bin of a twin-screw extruder, adding 1.0 parts of castor oil into a storage tank A connected to the melting section of the twin-screw extruder, adding 5.0 parts of MDI into a storage tank B connected to the plasticizing section of the twin-screw extruder, setting the temperature of the twin-screw extruder to 120-150° C., and starting the twin-screw extruder for mixing, melting, extruding, cooling, and pelletizing.
[0056] Example 9
[0057] The preparation method of the hydrophobic and tear-resistant biodegradable copolyester material of the present embodiment comprises the following steps: adding 94.0 parts of poly(hexamethylene terephthalate adipate) (MFR is 30-40 g / 10 min, and the molar ratio of terephthalic acid to adipic acid is 45:55) into a feeding bin of a twin-screw extruder, adding 4.0 parts of castor oil into a storage tank A connected to the melting section of the twin-screw extruder, adding 2.0 parts of MDI into a storage tank B connected to the plasticizing section of the twin-screw extruder, setting the temperature of the twin-screw extruder to 120-150° C., and starting the twin-screw extruder for mixing, melting, extruding, cooling, and pelletizing.
[0058] Comparative Example 1
[0059] The preparation method of the hydrophobic and tear-resistant biodegradable copolyester material of the present embodiment comprises the following steps: adding 94.0 parts of poly(hexamethylene terephthalate adipate) (MFR is 30-40 g / 10 min, and the molar ratio of terephthalic acid to adipic acid is 45:55) into the feeding bin of a twin-screw extruder, adding 2.0 parts of MDI into a storage tank B connected to the plasticizing section of the twin-screw extruder, setting the temperature of the twin-screw extruder to 120-150° C., and starting the twin-screw extruder for mixing, melting, extruding, cooling, and pelletizing.
[0060] Comparative Example 2
[0061] The preparation method of the hydrophobic and tear-resistant biodegradable copolyester material of the present embodiment comprises the following steps: adding 93.5 parts of poly(hexamethylene terephthalate adipate) (MFR is 30-40 g / 10 min, and the molar ratio of terephthalic acid to adipic acid is 45:55) into a feeding bin of a twin-screw extruder, adding 6.0 parts of castor oil into a storage tank A connected to the melting section of the twin-screw extruder, adding 0.5 parts of MDI into a storage tank B connected to the plasticizing section of the twin-screw extruder, setting the temperature of the twin-screw extruder to 120-150° C., and starting the twin-screw extruder for mixing, melting, extruding, cooling, and pelletizing.
[0062] The hydrophobic and tear-resistant biodegradable copolyester materials obtained in the above embodiments and comparative examples were subjected to resin water absorption experiments and performance tests after film blowing. The water absorption experiment was performed by setting the temperature of the constant temperature and humidity chamber to 65°C and the humidity to 85%. After the temperature and humidity in the constant temperature and humidity chamber were balanced, the test copolyester material was diluted and placed in the constant temperature and humidity chamber for exposure for 48 hours. The copolyester material was then taken out to measure the moisture content. The test method was based on GB / T32366-2015 Biodegradable Polybutylene Terephthalate-Adipate (PBAT); during film blowing, the screw machine temperature was 120-160°C, the die temperature was 170°C, the blow-up ratio was 3-4, and the film thickness was 25 μm; the test results are shown in Table 1.
[0063] Table 1 Test results of hydrophobic and tear-resistant biodegradable copolyester materials
[0064]
[0065]
[0066] In Examples 1-9, castor oil is introduced into the molecular structure of aliphatic-aromatic copolyester by isocyanate, and the obtained biodegradable copolyester material exhibits good hydrolysis resistance and tear resistance. In Comparative Example 1, poly(hexylene terephthalate adipate) is modified without using castor oil, and the hydrolysis resistance and tear resistance of the obtained polyester material are greatly reduced. In Comparative Example 2, poly(hexylene terephthalate adipate) is modified with more castor oil, which is difficult to be completely combined with the main chain of PBS molecule, and the remaining castor oil will precipitate or leach on the surface of the product, affecting the product's food contact certification.
[0067] Finally, it should be noted that the specific embodiments described herein are merely examples of the spirit of the present invention, and are not intended to limit the implementation methods of the present invention. Those skilled in the art of the present invention may make various modifications or supplements to the described embodiments or replace them in similar ways. It is not necessary and impossible to provide all examples of all implementation methods here. However, these obvious changes or modifications derived from the essential spirit of the present invention still fall within the scope of protection of the present invention, and interpreting them as any additional limitation is contrary to the spirit of the present invention.
Claims
1. A hydrophobic, tear-resistant biodegradable copolyester material, characterized in that: The invention comprises the following raw materials in parts by weight: 90 to 99 parts of aliphatic-aromatic copolyester, 0.5 to 5.0 parts of castor oil and 0.5 to 5.0 parts of isocyanate.
2. The hydrophobic, tear-resistant biodegradable copolyester material according to claim 1, characterized in that: Fatty-aromatic copolyesters are obtained by esterification and polycondensation of aromatic acids, fatty acids and alcohol compounds.
3. The hydrophobic, tear-resistant biodegradable copolyester material according to claim 2, characterized in that: The molar ratio of aromatic acid to fatty acid in the aliphatic-aromatic copolyester is 1-50:50-99.
4. The hydrophobic, tear-resistant biodegradable copolyester material according to claim 2, characterized in that: The molar amount of the alcohol compound is 1.0 to 5.0 times the sum of the molar amounts of the aromatic acid and the fatty acid.
5. The hydrophobic, tear-resistant biodegradable copolyester material according to claim 1, characterized in that: The melt flow rate of the aliphatic-aromatic copolyester at 190°C and a load of 2.16 kg is 20-100 g / 10 min.
6. The hydrophobic, tear-resistant biodegradable copolyester material according to claim 1, characterized in that: The carboxyl content in the aliphatic-aromatic copolyester is ≤30 mol / t.
7. The hydrophobic, tear-resistant biodegradable copolyester material according to claim 1, characterized in that: The isocyanate is one or more of diphenylmethane diisocyanate, toluene diisocyanate, hexamethylene diisocyanate, isophorone diisocyanate, and dicyclohexylmethane diisocyanate.
8. The hydrophobic, tear-resistant biodegradable copolyester material according to claim 1, characterized in that: The hydrophobic, tear-resistant biodegradable copolyester material also includes 0.0 to 0.5 parts of an initiator.
9. A method for preparing the hydrophobic, tear-resistant biodegradable copolyester material according to claim 1, characterized in that: The following steps are involved: Add the fat-aromatic copolyester into the feeding silo of the twin-screw extruder, add the castor oil into the storage tank A connected to the melting section of the twin-screw extruder, add the isocyanate into the storage tank B connected to the plasticizing section of the twin-screw extruder, and start the twin-screw extruder for mixing, melting, extrusion, cooling and pelletizing.
10. The preparation method according to claim 9, characterized in that: The temperature of the twin-screw extruder for mixing, melting and extruding is 120-180°C.